Expanding the role of nutrient-rich, hardy vegetables in home and community gardens in Quezon city - International Institute of Rural Reconstruction (CGIAR Science Program on Food Frontiers and Security, 2025)
Perennial vegetables—such as moringa (Moringa oleifera), papaya (Carica papaya), tree spinach (Cnidoscolus aconitifolius), sesbania (Sesbania grandiflora), Japanese malunggay (Sauropus androgynus), and malabar spinach (Basella alba)—offer multiple advantages. They thrive under irregular watering, require minimal inputs, and are better adapted to changing climates than annual species (Toensmeier, 2021). Studies show that perennial systems enhance soil fertility, sequester carbon, and strengthen smallholder resilience to climate shocks (Oelbermannl et al., 2024). Their year-round productivity and adaptability make them well-suited for small urban spaces, including vacant lots and vertical gardens.